Estudio para la implementación de estrategias de aprovechamiento privada del espacio público en zonas comerciales del municipio de Aguazul, departamento de Casanare. (2021)
The present work articulates directly with the research line of competitive cities and the sub-lines of territorial ordering or urban physical ordering, due to the incorporation of policies and strategies established and applied by main cities such as Bogotá, Medellín and Cali, which They were taken as an example for the development of this project, in order to achieve economic development in the different commercial modalities. Said policies or strategies are focused on the exploitation for the use of public space by the commercial sector, following some guidelines for conservation and uses to which they must be submitted to apply the characterization and achieve the benefit.